2022
DOI: 10.1186/s40537-022-00575-6
|View full text |Cite
|
Sign up to set email alerts
|

Stress detection using natural language processing and machine learning over social interactions

Abstract: Cyberspace is a vast soapbox for people to post anything that they witness in their day-to-day lives. Social media content is mostly used for review, opinion, influence, or sentiment analysis. In this paper, we aim to extend sentiment and emotion analysis for detecting the stress of an individual based on the posts and comments shared by him/her on social networking platforms. We leverage large-scale datasets with tweets to accomplish sentiment analysis with the aid of machine learning algorithms and a deep le… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(18 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…In addition, the IRS controller can communicate and coordinate with other network components (such as BS) through a separate feedback link, enabling low-rate information exchange. Figure 5 also shows an example of the structure of reflectors, each controlled by a switching diode [ 19 ]. By controlling the bias voltage through the DC feeder, the switching diode can be switched between “on” and “off” states, resulting in a phase difference of π .…”
Section: Augmented Reality and Volleyball Teachingmentioning
confidence: 99%
“…In addition, the IRS controller can communicate and coordinate with other network components (such as BS) through a separate feedback link, enabling low-rate information exchange. Figure 5 also shows an example of the structure of reflectors, each controlled by a switching diode [ 19 ]. By controlling the bias voltage through the DC feeder, the switching diode can be switched between “on” and “off” states, resulting in a phase difference of π .…”
Section: Augmented Reality and Volleyball Teachingmentioning
confidence: 99%
“…Therefore, according to LDA's logic, a textual document is composed of a distribution of such topics (Blei et al, 2003). The operation of LDA consists of creating a distribution of textual documents by topic, and a separate distribution of words by topic (Nijhawan et al, 2022).…”
Section: Lda Algorithm Application For Clusteringmentioning
confidence: 99%
“…Parameters α and η are parameters of Direchlet distributions. Parameter α controls the distribution of documents per topic and parameter η, the distribution of words per topic (Nijhawan et al, 2022). These parameters can be modified to obtain topics with more or fewer keywords, and documents composed of more or fewer topics.…”
Section: Anime Clustering For Automatic Classification and Configurat...mentioning
confidence: 99%
“…They had an F1-score of 84.3% for offensive language detection, 81.8% for hate speech detection, and 45.1% for fine-grained hate-speech recognition by applying BERT. BERT was used by Nijhawan et al for sentiment classification in their research [8]. Experiments revealed that, despite its comparatively simpler structure, the BERT model outperforms many prominent models in this subject.…”
Section: Literature Reviewmentioning
confidence: 99%